Prestasi Tim Futsal Kota Makassar Pada Pekan Olahraga Provinsi Ditinjau Dari Kondisi Fisik - Sulaeman Sulaeman; Yadi Jayadilaga (JURNAL STAMINA, 2023)
This study aims to examine the success of Futsal Athletes from Makassar City who won a gold medal at the 17th provincial performance in Bulukumba Sinjai Regency in terms of the physical condition of the players. The study is descriptive research. The sample in this study were 19 Makassar City Futsal Athletes. Data collection techniques in this study included several physical condition tests for futsal, namely the Multi Stage Fitness Test, Vertical Jump Test, 20 meter Run Test, Shuttle Run Test and Leg Dynamometer Test. The results showed that the average endurance of the Athletes was in the less category, while good category was found in the explosive power component. On the other hand, perfect category was experienced in the speed and agility component. Furthermore, the strength component showed a sufficient category. To sum up the 5 physical components needed, 3 physical components are above average and 2 physical components are below average.